Antibacterial and Cytotoxic Limonoids from the Seeds of Swietenia mahagony (Dhaka University Journal of Pharmaceutical Sciences, 2010)
Two limonoids, swietenine (1) and 3-O-tigloylswietenolide (2), were isolated from the chloroform soluble fraction of an ethanolic extract of Swietenia mahagony seed. The structures of these compounds were confirmed by spectroscopic methods, including both 1D and 2D NMR spectroscopy. The chloroform extract and the limonoids (1 and 2) exhibited moderate antibacterial activity against a series of Gram positive and Gram negative bacteria. The minimum inhibitory concentrations (MICs) of 1 and 2 were found to be in the range of 32-64 μg/ml against Bacillus megatorium and Escherichia coli. Compounds 1 and 2 were also assessed for preliminary cytotoxicity against brine shrimp and the LC50 values were found to be 14.6 and 12.5 μg/ml, respectively. Key words: Swietenia mahagony; Meliaceae; Limonoids; Swietenine; 3-tigloylswietenolide; Antibacterial activity; Cytotoxicity. DOI: 10.3329/dujps.v8i2.6028 Dhaka Univ. J. Pharm. Sci. 8(2): 141-145, 2009 (December)